Effects of high energy radiation on mechanical properties of PP/EPDM nanocomposite - Anuar, Hazleen; Jamal, Nur Ayuni; Abd Razak, Shamsul Bahri (Trans Tech Publications, Switzerland, 2011)
Nanocomposites are the materials that are created by introducing nanoparticulates that always referred to as filler into the matrix. Blends of polypropylene (PP)/ethylene propylene diene monomer EPDM)/Montmorillonite (MMT) were treated by compatibilizer MAPP and irradiation of electron beam. The effects on mechanical properties for both samples were compared with the untreated nanocomposites. Because each samples used different portion of clay loading, the effects of clay loading on mechanical properties is also observed. The sample is characterized by using Transmission Electron Microscope (TEM), X-Ray Diffraction (XRD), tensile test and impact test.